Validating MAS analysis models with the ASEME methodology. (2018) - Spanoudakis, Nikolaos I.; Floros, Efthymios; Mitakidis, Nektarios; Delias, Pavlos
When designing agent-oriented software, engineers should consider performance-related non-functional requirements. To this end, performance engineering practices provide a useful toolbox. In particular, simulation of the system's processes appears eminently suitable. Agent-oriented software engineering methodologies are not directly linked to process simulation features. This paper extends an AOSE methodology for transforming agent roles models to process models, and for streamlining the transformation process towards simulation. Our method allows process model generation, aiming to support the process simulation, and was integrated into a model-driven engineering methodology. We used an established process modelling notation (BPMN) as the target language for the process model, and we are able to deliver a ready-to-simulate model. Through simulation, an analyst can validate specific system requirements and test scenarios of how the system scales beyond the current requirements. Furthermore, because of process models familiarity within the business domain, engineers, managers and stakeholders can seamlessly communicate system designs.